Psychiatric comorbidities and adverse childhood experiences in women with self-reported polycystic ovary syndrome: An Australian population-based study. (June 2020) - Tay, Chau Thien; Teede, Helena J.; Loxton, Deborah; Kulkarni, Jayashri; Joham, Anju E.
Highlights: High prevalence of adverse childhood experience was observed in women with PCOS. Women with PCOS had lower level of social support and higher level of stress. PCOS is associated with many psychiatric disorders on top of anxiety or depression. Assessment and management of psychological health is necessary in PCOS. Abstract: Purpose: PCOS is associated with increased risk for depression and anxiety but its association with other psychiatric disorders is less clear, especially in community drawn populations. We aimed to investigate the prevalence of psychiatric disorders in women with PCOS and examine the factors associated with psychiatric disorders in this population. Method: A cross-sectional analysis of survey data was performed in community-recruited women born 1989−95 from the Australian Longitudinal Study of Women's Health (ALSWH). 760 and 7910 women with and without self-reported PCOS were included. The outcomes examined were self-reported depression, anxiety, post-traumatic stress disorder, bipolar affective disorder, obsessive compulsive disorder, borderline personality disorder and other disorders. The main explanatory variable was self-reported PCOS status. Other factors examined included adverse childhood experience scale (ACES), social support, perceived stress, sociodemographic and lifestyle factors. Chi-square tests were used to examine the differences in prevalence between groups. Logistic regression analyses were performed to assess factors associated with psychiatric disorders. Results: Women with PCOS reported a significantly higher prevalence of the psychiatric disorders examined, compared with women without PCOS. PCOS was significantly associated with depression (adjusted odds ratio (OR) 1.4, 95 % confidence interval (CI) 1.2−1.7), anxiety (adjusted OR 1.2, 95 % CI 1.0−1.5), post-traumatic stress disorder (adjusted OR 1.5, 95 % CI 1.1−1.9) and obsessive compulsive disorder (adjusted OR 1.8, 95 % CI 1.2−2.5). More women with PCOS reported adverse childhood experiences (ACES ≥4: 19.3 % vs 9.2 %) and this was the strongest factor associated with psychiatric disorders (ACES ≥4: adjusted OR 2.9, 95 % CI 2.4−3.5). Conclusions: Women with PCOS had higher prevalence of various psychiatric conditions and adverse childhood experiences compared with women without PCOS. ACES was the strongest correlate of psychiatric disorders. These findings support PCOS is a reproductive, metabolic and psychological disorder and reinforces guideline recommendations to assess psychological wellbeing for in women with PCOS.